Immunosenescence, aging and successful aging - Wang, Yunan; Dong, Chen; Han, Yudian; Gu, Zhifeng; Sun, Chi (Frontiers in Immunology, 2022)
Aging induced a series of immune related changes, which is called immunosenescence, playing important role in many age-related diseases, especially neurodegenerative diseases, tumors, cardiovascular diseases, autoimmune diseases and coronavirus disease 2019(COVID-19). However, the mechanism of immunosenescence, the association with aging and successful aging, and the effects on diseases are not revealed obviously. In order to provide theoretical basis for preventing or controlling diseases effectively and achieve successful aging, we conducted the review and found that changes of aging-related phenotypes, deterioration of immune organ function and alterations of immune cell subsets participating in the process of immunosenescence, which had great effects on the occurrence and development of age-related diseases.